An High Equipped Data Hiding Algorithm Based On Secret Fragment Visible Mosaic Images And Pixel Color Transformations For Secure Image Transmission (International Journal of Engineering and Computer Science, 2018)
Hiding the data in digital images has been area of interest in the digital image processing domain. Although so much work has been carried out in the literature to resolve the issues like increasing the data capacity, creating the secret image alike of target image but most of the works fails to meet the practical requirements. This paper presents an approach where mosaic image generation has done by dividing the secret image into fragments and transforming their respective color characteristics into corresponding blocks of the target image. Usage of the Pixel color transformations helps to yield the lossless recovered image based on the untransformed color space values. Generation of the key plays an important role to recover the data from the secret image in lossless manner. Finally the same approach can be performed on videos also which helps to eliminate the flickering artifact to achieve the lossless data recovery in motion related videos. The experimental results shows good robust behavior against all incidental and accidental attacks and compare to the conventional algorithms Performance evaluation has been increased in a significant way.